The Influence of Green Accounting, Tax Aggressiveness and Media Exposure on Corporate Social Responsibility Disclosure - Triana, Zhenata Rizki; Septiawati, Rohma; Rachpriliani, Awaliawati (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2024)
Environmental and Social Responsibility is a vital aspect that every company must address to create sustainable profits. Factors influencing corporate social responsibility disclosure include green accounting, tax aggressiveness, and media exposure. This quantitative study is designed to explore the impact of green accounting, tax aggressiveness, and media exposure on corporate social responsibility disclosure. Using secondary data from 80 LQ45 companies listed on the Indonesia Stock Exchange during the 2019-2022 period, this study applied purposive sampling and Structural Equation Modeling-Partial Least Square (SEM-PLS) analysis using SmartPLS 3 software. The findings show that green accounting and tax aggressiveness have a positive influence on corporate social responsibility disclosure, while media exposure has no meaningful influence. This indicates that sustainable accounting practices and companies' strategies to reduce their tax burden aggressively contribute positively to their CSR transparency